2023
DOI: 10.1371/journal.pgph.0002449
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to improve interpersonal communication along the continuum of maternal and newborn care: A scoping review and narrative synthesis

Klaartje M. Olde Loohuis,
Bregje C. de Kok,
Winter Bruner
et al.

Abstract: Effective interpersonal communication is essential to provide respectful and quality maternal and newborn care (MNC). This scoping review mapped, categorized, and analysed strategies implemented to improve interpersonal communication within MNC up to 42 days after birth. Twelve bibliographic databases were searched for quantitative and qualitative studies that evaluated interventions to improve interpersonal communication between health workers and women, their partners or newborns’ families. Eligible studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 191 publications
0
3
0
Order By: Relevance
“…Lack of communication and autonomy during childbirth is a serious concern and should be tackled to improve women's experience. A recent review showed that communication skills can be enhanced by training and using additional communication tools, however, the importance of an enabling environment cannot be underestimated (42). The health care system in which health providers operate undoubtedly impacts the ability to effectively communicate and respect women's choices.…”
Section: Predictors Of Qmnc Indexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of communication and autonomy during childbirth is a serious concern and should be tackled to improve women's experience. A recent review showed that communication skills can be enhanced by training and using additional communication tools, however, the importance of an enabling environment cannot be underestimated (42). The health care system in which health providers operate undoubtedly impacts the ability to effectively communicate and respect women's choices.…”
Section: Predictors Of Qmnc Indexesmentioning
confidence: 99%
“…The health care system in which health providers operate undoubtedly impacts the ability to effectively communicate and respect women's choices. Enabling factors can include a non-excessive workload (allowing time to communicate), availability of adequate space and resources, and a work atmosphere where teamwork, empathy and good communication are the norm (42). More research into these environmental factors and providers' perspectives is highly needed in the Belgian context to tackle these shortcomings in childbirth care.…”
Section: Predictors Of Qmnc Indexesmentioning
confidence: 99%
“…Previous studies have found that integrating infant and young child nutrition counseling during antenatal care (ANC), postnatal care, family planning or child consultation visits can be an effective approach to improving infant and young child feedings in some settings [6][7][8]. However, findings from a scoping review and narrative analysis published in 2023 found that strategies to improve interpersonal communication along the continuum of maternal and newborn care centered around information sharing and that women, their partners and families could benefit from a more comprehensive, integrated communication strategy [9]. Integrated social and behavior change (SBC) programming is an evidence-driven approach that aims to affect key behaviors and social norms by addressing their individual, social, and structural determinants (factors).…”
Section: Introductionmentioning
confidence: 99%